A high signal-to-noise HST spectrum towards J1009+0713: precise absorption measurements in the CGM of two galaxies. Issue 1 (1st August 2019) - Lochhaas, Cassandra; Mathur, Smita; Frank, Stephan; Som, Debopam; Krongold, Yair; Kulkarni, Varsha; Weinberg, David H; Nicastro, Fabrizio; Gupta, Anjali
ABSTRACT: High signal-to-noise spectra towards background quasars are crucial for uncovering weak absorption in the circumgalactic medium (CGM) of intervening galaxies, such as the diagnostic lines of N v that provide insight to the ionization process of warm gas but typically have low equivalent widths. We present a new spectrum from the Hubble Space Telescope with a signal-to-noise ratio of ∼20–35 towards the quasar SDSS J1009+0713 and analyse absorption systems in the CGM of two L ⋆ galaxies close to the line of sight. We identify additional absorption in the CGM of these galaxies that was not reported by the previous lower signal-to-noise spectrum, as well as Milky Way absorbers and quasar outflows from J1009+0713. We measure log ( N N v / N O  vi ) ∼ −1.1 for two CGM absorbers, inconsistent with gas in collisional ionization equilibrium and consistent with a radiatively cooling bulk flow of ∼50–150 km s −1, which could be produced by galactic winds. These column density ratios are also consistent with those found for other L ⋆ galaxies and for some gas in the Milky Way's halo. We place upper limits of log ( N N v / N O vi ) < −1.8 to −1.2 for other O vi absorbers in the same haloes, which suggests that O vi is produced by different processes in different parts of the CGM, even within the same galactic halo. Together with the kinematically different structure of high- and low-ionization lines, these results indicate there are many components to a single galaxy's gaseous halo. We find the redshift number density of Ly α forest absorbers and broad Ly α absorbers are consistent with expectations at this redshift.